2015
DOI: 10.1016/j.psym.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Co-morbid Symptoms of Depression and Anxiety With All-Cause Mortality and Cardiac Rehospitalization in Patients With Heart Failure

Abstract: Background Patients with heart failure (HF) experience multiple psychological symptoms. Depression and anxiety are independently associated with survival. Whether co-morbid symptoms of anxiety and depression are associated with outcomes in patients with HF is unknown. Objective To determine whether co-morbid symptoms of depression and anxiety are associated with all-cause mortality or rehospitalization for cardiac causes in patients with HF. Method A total of 1,260 HF patients participated. Cox regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 37 publications
0
37
0
5
Order By: Relevance
“…A recent systematic review and meta-analysis (Sokoreli et al, 2016) provided an update review of studies that evaluated the effect of depression on mortality among HF patients. Depression has been associated with decreased survival in HF patients mainly in short term follow-up, that is: in 72.5 days ; 90 days (Albert et al, 2009); 6 months ; 12 months (Alhurani et al, 2015;Cully et al, 2009;Jiang et al, 2001;Rollman et al, 2012); 18 months (Coyne et al, 2001;Faller et al, 2015;Lesman-Leegte et al, 2009;Moraska et al, 2013); 24 months (Murberg et al, 1999;Faris et al, 2002;Friedmann et al, 2006;Kato et al, 2009;Smith et al, 2012) and 3 years (Jiang et al, 2007;Junger et al, 2005;Volz et al, 2011;Konstam et al, 1996;Sherwood et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis (Sokoreli et al, 2016) provided an update review of studies that evaluated the effect of depression on mortality among HF patients. Depression has been associated with decreased survival in HF patients mainly in short term follow-up, that is: in 72.5 days ; 90 days (Albert et al, 2009); 6 months ; 12 months (Alhurani et al, 2015;Cully et al, 2009;Jiang et al, 2001;Rollman et al, 2012); 18 months (Coyne et al, 2001;Faller et al, 2015;Lesman-Leegte et al, 2009;Moraska et al, 2013); 24 months (Murberg et al, 1999;Faris et al, 2002;Friedmann et al, 2006;Kato et al, 2009;Smith et al, 2012) and 3 years (Jiang et al, 2007;Junger et al, 2005;Volz et al, 2011;Konstam et al, 1996;Sherwood et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among the psychological factors, depression was found to be an important determinant influencing rehospitalisation (Suzuki et al, 2014). Many studies showed that HF patients simultaneously experience depression; indeed, the prevalence of depression was reported to range from 15%-40% in HF patients in Western countries (Rutledge, Reis, Linke, Greenberg, & Mills, 2006;O'Connor et al, 2008;Alhurani et al, 2015). About 20% of HF patients were diagnosed with major depressive disorder (Liu & Ziegelstein, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Estes fatores estão também associados a mudanças siopatológicas, tais como a hipercortisolemia, alteração da função plaquetária, redução da variabilidade da frequência cardíaca e arritmias cardíacas, as quais podem levar à hospitalização e à morte. Deste modo, infere-se que estes fatores quando associados à ansiedade e/ ou à depressão contribuem continuamente para uma alta cormobilidade e mortalidade dos indivíduos com DCV (Alhurani et al, 2015;Doering et al, 2010;Sher et al, 2010). O facto dos indivíduos com idade mais avançada apresentarem níveis mais elevados de depressão, não constituiu surpresa para nós.…”
Section: Discussionunclassified
“…Diversas consequências advêm da presença da ansiedade e da depressão nos indivíduos com DCV, nomeadamente no que se refere à menor adesão ao regime terapêutico, aos programas de reabilitação e a comportamentos de manutenção e gestão do autocuidado. De entre elas destacam-se ainda a exacerbação dos fatores de risco tradicionais, a menor qualidade de vida, a maior probabilidade de novos e recorrentes eventos cardíacos decorrentes de alterações siopatológicas, a exacerbação de outras comorbilidades, a diminuição das capacidades cognitivas e do senso de controlo (Alhurani et al, 2015;Doering et al, 2010;Sher, Lolak & Maldonado, 2010). Outra área que também tem vindo a ser alvo de investigação, refere-se à perceção que os indivíduos com DCV têm sobre a saúde, através do estudo do construto controlo percebido.…”
Section: Introductionunclassified